Vestibulo-Oral inclination of maxillary and mandibular canines and bicuspids - a CBCT investigation. Issue 1 (December 2016) - Hourfar, Jan; Bister, Dirk; Lisson, Jörg; Goldbecher, Christine; Ludwig, Björn
Abstract Background The aim of this retrospective study was to measure tooth and crowns axes of canines, first and second bicuspids of orthodontically untreated subjects with near normal occlusion to: 1. Define norms and reveal potential gender differences and 2. Discuss implications of the findings for orthodontics. Methods The CBCT-datasets of 167 patients, 56 males (mean age 28.63 years ± 11.99 years) and 111 females (mean age 29.72 years ± 11.47 years) were used. Tooth- and crown axes were measured for right and left sides. Normal distribution was evaluated with the Kolmogorov-Smirnov-test. For gender comparison independent t-Tests and for comparison of right and left sides a pairedt -Test were used for normally distributed data. For data not following normal distribution for gender comparison the Mann-Whitney-U-Test was used and for data comparing the two sides the Wilcoxon signed rank test was applied. The level of statistical significance was set atp  ≤ 0.05. Results Measurement of tooth axes revealed buccal inclination for both genders with maximum values for maxillary and mandibular canines. Statistical significant differences were only found for maxillary canines (P  = 0.025) and lower second bicuspids (P  = 0.016) respectively. Values for crown axes revealed oral inclination for both genders with maximum values for maxillary first bicuspids and in the mandible for first and second bicuspids. No statistical significant differences were found between the genders apart from asymmetry for crown axes for the upper first bicuspids for males (P  = 0.006) and females (P  < 0.001). Conclusions Our study reveals that irrespective of gender, oral inclination of the crowns of canines and premolars is the norm. The values of the most commonly used bracket prescriptions coincide with the average values found in our investigation. For esthetic reasons modifications of torque values can be considered.